Chemodiversity in Selaginella: a reference system for parallel and convergent metabolic evolution in terrestrial plants - Weng, Jing-Ke; Noel, Joseph P. (Frontiers in Plant Science, 2013)
Early plants began colonizing the terrestrial earth approximately 450 million years ago. Their success on land has been partially attributed to the evolution of specialized metabolic systems from core metabolic pathways, the former yielding structurally and functionally diverse chemicals to cope with a myriad of biotic and abiotic pressures. Over the past two decades, functional genomics, primarily focused on flowering plants, has begun cataloging the biosynthetic players underpinning assorted classes of plant specialized metabolites. However, the molecular mechanisms enriching specialized metabolic pathways during land plant evolution remain largely unexplored. Selaginella is an extant lycopodiophyte genus representative of an ancient lineage of tracheophytes. Notably, the lycopodiophytes diverged from euphyllophytes over 400 million years ago. The recent completion of the whole-genome sequence of an extant lycopodiophyte, Selaginella moellendorffii, provides new genomic and biochemical resources for studying metabolic evolution in vascular plants. 400 million years of independent evolution of lycopodiophytes and euphyllophytes resulted in numerous metabolic traits confined to each lineage. Surprisingly, a cadre of specialized metabolites, generally accepted to be restricted to seed plants, have been identified in Selaginella. Initial work suggested that Selaginella lacks obvious catalytic homologues known to be involved in the biosynthesis of well-studied specialized metabolites in seed plants. Therefore, these initial functional analyses suggest that the same chemical phenotypes arose independently more commonly than anticipated from our conventional understanding of divergent evolution of metabolism. Notably, the emergence of analogous and homologous catalytic machineries through convergent and parallel evolution, respectively, seems to have occurred repeatedly in different plant lineages.